HPV pseudovirion production in plants - Kennedy, Paul (Department of Molecular and Cell Biology, 2014)
Human papilloma virus (HPV) infection is the most common etiological agent of cervical cancer, the most common cancer in women in Africa. The lifecycle of HPV has historically made the virus difficult to culture in vitro, and this has hindered the study of the virus, as well as development of vaccines. The development of synthetic HPV particles, such as virus-like particles (VLPs) and more recently pseudovirions (PsVs), has allowed for unprecedented insights into the lifecycle and immunology of this virus. This has led to the development of two currently available vaccines, namely Cervarix™ and Gardasil®. Cervarix offers protection against high-risk HPV types 16 and 18, while Gardasil offers further protection against types 6 and 11. Both of these vaccines are based on major capsid protein L1 Virus-like particles (VLPs). While these vaccines show no loss of efficacy, further work is underway to develop a second generation HPV vaccine that is cheap, stable and displays cross-neutralising activity across a broader range of HPV types. The recent efficient methods for intracellular production of HPV PsVs encapsidating nonpapillomaviral DNA (pseudogenomes) has allowed for development of a robust and sensitive pseudovirion-based neutralisation assay (PBNA), which has become the gold standard neutralisation assay for the testing of candidate HPV vaccines. The currently accepted PsV production method utilises mammalian cell culture to produce HPV PsVs, encapsidating a SEAP reporter plasmid, at high titres. While this is an effective method of PsV production, mammalian cell culture is expensive and time-consuming. Transient recombinant protein expression in plants offers a rapid and cost-effective alternative to mammalian cell culture. Here, we developed a method of high-titre HPV PsV production in plants. The autonomously replicating plant vector, pRIC3, was modified to include mammalian reporter cassettes encoding luc or SEAP, for the production of reporter pseudogenomes DNA in plants by Agrobacterium-mediated transient expression. The SEAP and luc cassettes were introduced into pRIC3 upstream of the plant cassette, which was included only to increase the final pseudogenome size for efficient packaging into PsVs. The SEAP cassette was also introduced into pRIC3 in place of the plant cassette, to form a smaller pseudogenome. Thus three vectors were created, namely pRIC3-mSEAP+ (6.4Kbp pseudogenome), pRIC3-mluc+ (7.4Kbp pseudogenome), and pRIC3-mSEAP (4.8Kbp pseudogenome), which would produce pseudogenomes that covered the full range of plasmid sizes incorporated by assembling HPV capsid proteins in vivo. All three replicating vectors demonstrated the formation of a replicon, and autonomous replication, in Nicotiana benthamiana plants. Each of these vectors were co-infiltrated with the non-replicating transient plant expression constructs pTRAc-hL1 and pTRAc-hL2, which encode human-codon optimised forms of HPV-16 major and minor capsid proteins, respectively. It was expected that encapsidation of replicon DNA as a pseudogenome into assembling HPV particles would result in the production of HPV PsVs in planta. In addition, L1 and L2 were expressed in the absence of replicon DNA to form L1/L2 VLPs. Particles were extracted from plant material at four days post-infiltration, using a modified VLP extraction protocol. HPV particles were separated on the basis of isopycnic caesium chloride density gradient ultracentrifugation, dialysed against high-salt PBS and identified by fractionation and probing with an anti-L1 antibody. Particles corresponding to the buoyant density of pseudovirions were seen in samples with or without replicon DNA. Western blotting showed that all particles had incorporated both L1 and L2 proteins. Particles were digested with proteinase K to release encapsidated pseudogenome DNA and PCR confirmed the presence of replicon-specific DNA in each PsV. Electron microscopy confirmed the presence of HPV-16 PsVs in all samples. To test whether plant-produced HPV-16 PsVs could be used in pseudovirion-based neutralisation assays, mammalian cells were pseudoinfected with purified mSEAP, mSEAP+ or mluc+ PsVs. mSEAP and mluc+ PsVs elicited a reporter gene response in mammalian cells 72 hours post-infection using SEAP and luciferase assays, respectively, while mSEAP+ PsVs showed no reporter gene expression in mammalian cells. PsVs incubated with a known HPV-16 neutralising antibody showed partial neutralisation of mSEAP PsVs and complete neutralisation of mluc+ PsVs To our knowledge, this is the first demonstration of production of HPV PsVs in plants, and their use in a PBNA. Further, it is the first demonstration of production of HPV L1/L2 VLPs in plants. While much work remains to improve plant production and purification methods of PsVs, as well as mammalian expression following PsV pseudoinfection, this is an important step towards a new method of PsV production.